Le sarcophage de pierre du haut Moyen Âge, des critères pour une étude - Fabrice Henrion (Les Cahiers de l'École du Louvre)
Over the last two decades, the study of Early Middle Ages stone sarcophagi has taken a particular turn: the “object” itself is now worthy of consideration, not only its decoration, thus revealing the distinguishing characteristics that were often that were previously too often left aside. Thus, by considering the whole of its history, from its quarry of origin to the necropolis, cemetery or place of worship that finally received it, it is now possible to place any specimen, whole or fragmentary, within an archaeologically established typology and chronology. While the decoration had to be put aside during the elaboration of the typological and chronological classification method, we naturally returned to it, through the prism of previous studies and the contribution of new data.